Rencana lansekap wisata berbasis aspek 4-A di kawasan pesisir Batu Bolong, Desa Canggu, Kabupaten Badung, Provinsi Bali - Astuti, Ayu Ratih Widhi; Gunadi, I Gusti Alit; Utami, Ni Wayan Febriana (Jurnal Arsitektur Lansekap, 2018)
Landscape tourism plan based on aspect of 4-A at Batu Bolong coastal area, Canggu Village, Badung Regency, Bali Provice. Badung regency is a place that has spacious coastal landscape and much developed for tourist area. However, its potential needs to be optimized. One of attractive coastal area in Badung is Batu Bolong which is located in Canggu village, North Kuta district. Tourism is a commodity product which is created to respond to the society needs by considering four basic aspects that have to be met as a totality product. This research aims to explore both potencies and constraints within the Batu Bolong coastal area towards tourism development so it would be able to determine development planning concept based on aspect of 4-A (attractions, accessability, amenities, ancilliary) offering concept. The research method used consists of several stages i.e. inventory, analysis, synthesis and concept. The results show that based on the inventory and analysis of biophysical, socio-cultural and 4-A aspects of tourism offer on the landscape development were produce a spatial concept, concept circulation, greenery concept and finally resulted a block plan of 4-A aspect-based landscape management plan. This concept will be support the activities of the marine and religious tourism plan in Batu Bolong.